Simplify the following expression:
lo g 2 ( 2 0 1 9 ! ) 1 + lo g 3 ( 2 0 1 9 ! ) 1 + lo g 4 ( 2 0 1 9 ! ) 1 + ⋯ + lo g 2 0 1 9 ( 2 0 1 9 ! ) 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Each of the terms of the sum can be rewritten using lo g b 2 0 1 9 ! 1 = lo g 2 0 1 9 ! lo g b
Hence the sum is lo g 2 0 1 9 ! lo g 2 + lo g 3 + ⋯ + lo g 2 0 1 9 = lo g 2 0 1 9 ! lo g 2 0 1 9 ! = 1
Problem Loading...
Note Loading...
Set Loading...
S = lo g 2 2 0 1 9 ! 1 + lo g 3 2 0 1 9 ! 1 + lo g 4 2 0 1 9 ! 1 + ⋯ + lo g 2 0 1 9 2 0 1 9 ! 1 = lo g 2 0 1 9 ! lo g 2 + lo g 2 0 1 9 ! lo g 3 + lo g 2 0 1 9 ! lo g 4 + ⋯ + lo g 2 0 1 9 ! lo g 2 0 1 9 = lo g 2 0 1 9 ! lo g 2 + lo g 3 + lo g 4 + ⋯ + lo g 2 0 1 9 = lo g 2 0 1 9 ! lo g 2 0 1 9 ! = 1 By lo g b a = lo g b lo g a As lo g a + lo g b + lo g c + ⋯ + lo g z = lo g ( a b c ⋯ z )